Step-by-step guide for electrochemical generation of highly oxidizing reactive species on BDD for beginners - Castillo-Cabrera, G. Xavier; Pliego-Cerdán, Caroline I.; Méndez, Erika; Espinoza-Montero, Patricio J. (Frontiers in Chemistry, 2024)
Selecting the ideal anodic potential conditions and corresponding limiting current density to generate reactive oxygen species, especially the hydroxyl radical (•OH), becomes a major challenge when venturing into advanced electrochemical oxidation processes. In this work, a step-by-step guide for the electrochemical generation of •OH on boron-doped diamond (BDD) for beginners is shown, in which the following steps are discussed: i) BDD activation (assuming it is new), ii) the electrochemical response of BDD (in electrolyte and ferri/ferro-cyanide), iii) Tafel plots using sampled current voltammetry to evaluate the overpotential region where •OH is mainly generated, iv) a study of radical entrapment in the overpotential region where •OH generation is predominant according to the Tafel plots, and v) finally, the previously found ideal conditions are applied in the electrochemical degradation of amoxicillin, and the instantaneous current efficiency and relative cost of the process are reported.